Formulation and optimization of Naringin loaded ß-lactoglobulin nanoparticles - Kumar, Satyawrath; Kalra, Naresh (Journal of Neonatal Surgery, 2025)
Protein derived from food-based nanoparticles are of great interest as they are recognized as safe and are easy to prepare. In this work we prepared ß- lactoglobulin nanoparticles for the improved bioavailability of naringin. The effect of pH, temperature, heating time and drug to protein ratio was optimized for particle size, PDI and encapsulation efficiency. The morphological features of the prepared particle revealed smooth spherical particles in clusters. The average particle size of the formulations ranged between 227 nm to 407 nm and the PDI ranged from 0.213 to 0.711. The zeta potential of the prepared ß-Lg nanoparticles was found in the range -4.1 to -7.4 mV suggestive to particle aggregation and the observed size range. The encapsulation of naringin was found in the range of 12.5% to 38.6%. The best formulation (F1) exhibited an encapsulation efficiency of 38.6% with particle size 227 nm and PDI 0.213. The in vitro release of F1 exhibited controlled release of naringin from the nanoparticles for 12 h. The results of the study led to the conclusion that protein nanoparticles (ß-lacotoglobulin) could be an effective method to improve bioavailability of phytomolecules.